Setulang village protects its river: Ramses Iwan on behalf of the Setulang community - Iwan, R. (2003)
The Setulang community in Malinau, Indonesia has resisted offers of substantial sums of money from timber companies to gain access to their lands. Instead they have sought to conserve their forest because of the many services it provides them. This article, written by a member of the Setulang community, explains the background of this case of community conservation in Borneo.